Secreted Frizzled-Related Protein 5 in Serum and Urine of Post-Partum Women with Gestational Diabetes Mellitus - Marcin Trojnar; Żaneta Kimber-Trojnar; Bożena Leszczyńska-Gorzelak (Journal of Education, Health and Sport, 2019)
Secreted frizzled-related protein 5 (SFRP5) is a newly identified member of the SFRP family produced by the adipose tissue which can act as an anti-inflammatory adipokine. The aim of the study was to assess SFRP5 levels in the serum and urine of women with gestational diabetes mellitus (GDM) in the early post-partum period with reference to their laboratory test results, body composition and hydration status. The study subjects included two groups: 22 GDM patients and 24 healthy controls. Maternal body composition and hydration status were evaluated by the bioelectrical impedance analysis (BIA) method. The serum and urine SFRP5, leptin and ghrelin concentrations were determined via enzyme-linked immunosorbent assay (ELISA). No significant differences were observed between the GDM and healthy groups with regard to the serum and urine SFRP5 concentrations. In the GDM group serum and urine SFRP5 levels correlated positively. The serum SFRP5 concentrations correlated negatively with hemoglobin A1c (HgbA1c) and leptin serum levels in the controls. In the control and GDM groups the serum and urine SFRP5 levels correlated negatively with the serum ghrelin levels. It appears that ghrelin as well as SFRP5 could influence the metabolic homeostasis 48 hours after delivery. A significant correlation between concentrations of SFRP5 in the serum and urine seems to suggest that urine sampling may represent an alternative to the current standard of management i.e. blood sampling. Further research in this field is required.